3D printing of PLA composites scaffolds reinforced with keratin and chitosan: Effect of geometry and structure. (5th December 2020) - Rojas-Martínez, L.E.; Flores-Hernandez, C.G.; López-Marín, L.M.; Martinez-Hernandez, A.L.; Thorat, S.B.; Reyes Vasquez, C.D.; Del Rio-Castillo, A.E.; Velasco-Santos, C.
Graphical abstract: Highlights: PLA, chitosan and keratin can be used to make scaffolds by extrusion and 3D printing. Particles as reinforcement have a better performance compared to fibers. Chitosan and keratin promote important increase of cell growth in a PLA matrix. Alpha and beta keratin structures have a similar performance in cell growth. 3D printing proved be able to make composite scaffolds applied in tissue engineering. Abstract: We have used polylactic acid (PLA), keratin and chitosan to manufacture 3D printable polymer composite scaffolds. The effect of two different keratin reinforcements types, i.e., keratin in fibers and particles form are studied, and the size reduction in chitosan material. Specifically, the behaviour of two different keratin configurations i.e., α-helix (from hair) and predominantly β-sheet (from chicken feathers) are used. The 3D printed composites are analysed by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and dynamic mechanical analysis (DMA). Finally, cytotoxicity assays and swelling tests are performed to analyse the possible application in tissue engineering. Different keratin and chitosan sizes and shapes analyses revealed that morphology is of paramount importance for thermomechanical and cellular growth. Achieving the best results with particle-like shaped rather than with fibre-like, and chitosan materials before of size reduction. For example, the storage modulus increases around 80–85% and the cell growth results increase approximately 81–85%. In addition, swelling tests in distilled water and simulated body fluid (SBF) reveal, particle size is also important to avoid excessive swelling in the composites. Thus, the results presented evidence about the impact of reinforcement size in the studied properties the feasibility of developing biodegradable polymer composites of completely natural sources and their application for bio-scaffolds supported by the versatility of additive manufacturing.